Pengaruh Literasi Keuangan Dan Financial Technology Terhadap Inklusi Keuangan Pada Pelaku UMKM Sektor Olahan Makanan Dan Minuman Di Kecamatan Tampan Kota Pekanbaru - Rissayana Rissayana; Mariaty Ibrahim (eCo-Buss, 2023)
The objective of this research is to examine the impact of financial literacy and financial technology on financial inclusion. The study utilizes a quantitative research method and incorporates both primary and secondary data. The primary data was collected through a questionnaire consisting of 24 questions, which was completed by MSME owners in the processed food and beverage industry. The sample was selected using a purposive random sampling technique from a population of 1,856 business owners. Data analysis involved descriptive statistics, validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression testing, t-testing, f-testing, and determination coefficient testing. The data analysis was conducted using SPSS 25 software. (1) financial literacy significantly impacts financial inclusion, (2) financial technology significantly affects financial inclusion, and (3) financial literacy and financial technology collectively exert a significant influence on financial inclusion among MSME actors in the food and beverage sector in Tampan District.